Role of Individual, Family, and Peers in Sexual Initiation Among Late Adolescents Attending Institutions of Higher Learning in Malaysia - Samad, S.A.; Hairi, N.N.; Ismail, M. (SAGE Publications (UK and US), 2016)
This cross-sectional study aimed to determine the prevalence and the factors associated with sexual initiation among the late adolescents in 6 institutions of higher learning in Malaysia. A total of 1572 students completed self-administered questionnaires between April and September 2013. Hierarchical multivariate logistic regression analyses stratified by gender were employed to identify the correlates of sexual initiation. The analyses were further adjusted by sampling weights. The overall prevalence of sexual initiation was 9.8% (95% confidence interval [CI] = 8.3-11.6), 18.1% (95% CI = 15.1-21.5) among males, and 4.1% (95% CI = 2.9-5.9) among females. The risk factors identified in this study supported the influence of the individual, family, and peer factors in the social-ecological model on adolescents' behaviors. The findings suggest the need for risk-reduction strategies aimed at the individual, family, and peer levels as well as the importance of gender-specific focus in assuring better outcomes.